Population Pharmacokinetics of Intravenous Amoxicillin Combined With Clavulanic Acid in Healthy and Critically Ill Dogs - Vegas Cómitre, Maria D.; Cortellini, Stefano; Cherlet, Marc; Devreese, Mathias; Roques, Beatrice B.; Bousquet-Melou, Alain; Toutain, Pierre-Louis; Pelligand, Ludovic (Frontiers in Veterinary Science, 2021)
Background – Data regarding antimicrobial pharmacokinetics (PK) in critically-ill dogs is lacking and likely differs from healthy dogs. The aim of this work is to describe a population PK model for IV amoxicillin clavulanic acid (AMC) in both healthy and sick dogs and to simulate a range of clinical dosing scenarios to compute PK/PD cut-offs for both populations. Methods – Prospective clinical trial in normal and critically ill dogs. Twelve client-owned dogs hospitalized in the intensive care unit (ICU) received IV AMC 20 mg/kg every 8 hours (0.5 h infusion) during at least 48 hours. Eight blood samples were collected at pre-determined times, including 4 trough samples before the next administration. Clinical covariates and outcome were recorded, including survival to discharge and bacteriologic clinical failure. Satellite PK data was obtained de novo from a group of Twelve healthy research dogs, dosed with a single AMC 20 mg/kg IV. Non-linear mixed effect model was used to estimate the PK parameters (and the effect of health upon them) together with variability within- and between-subjects. Monte Carlo simulations were performed with 7 dosage regimens (standard and increased doses). Correlation between model-derived drug exposure and clinical covariates were tested with Spearman nonparametric correlation analysis. Outcome was recorded including survival to discharge and bacteriologic clinical failure. Results – Total of 218 amoxicillin concentrations in plasma were available for healthy and sick dogs. Tricompartmental model best described the data. Amoxicillin clearance was reduced by 56% in sick dogs (0.147 L/kg/h) compared to healthy dogs (0.336 L/kg/h). Intercompartmental clearance was also decreased. None of the clinical data covariates were significantly correlated with individual exposure. Monte Carlo simulations showed that higher PK/PD cut-off values of 8 mg/L could be reached in sick dogs by extending the infusion to 3h or doubling the dose. Conclusions – The PK of AMC is profoundly different in critically ill dogs compared to normal dogs, with much higher inter-individual variability and a lower systemic clearance. Our study allows to generate hypotheses with regards to higher AMC exposure in clinical dogs and provides supporting data to revise current AMC clinical breakpoint for IV administration.